GENDING PENGIRING ABDI DALEM CITRALATA DAN PRALATA DALAM UPACARA GAREBEK DI KERATON YOGYAKARTA - Saptono, Saptono (ADISAM PUBLISHER, 2025)
The research aims to describe the role of gendhing as an accompaniment to Abdi Dalem (court servants) Lurah Citralata and Pralata during ceremonial events at The Sultanate of Yogyakarta in the modern era, specifically during the reign of Sri Sultan Hamengku Bawono ka-10. To date, there has been limited research that specifically estimates this Citralata and Pralata court servants in the context of revitalization, particularly during the Garebek ceremony. The emergence of the Citralata and Pralata court servants has become a notable spectacled for the public especially when witnessed first hand. this occurrence has left a fresh impression as in a few decades the Citralata and Pralata court servants have not been featured in ceremonial events. For this reason, this paper aimed to provide insight into their presence and significance. In addition, the study examines the musical instruments used, the presentation and its meaning, as well as the structure of the accompanying gamelan composition for the Citralata and Pralata court servants. the research adopts a qualitative, descriptive-analytical approach, including literature review and interviews with royal servants directly involved in the Garebek ceremony. The research indicate that the gamelan, composition pattern, and gendhing presentation have undergone reconstruction and change. Nevertheless, it can be concluded that this element remains a supporting aspect of the Garebek ceremony, primarily intended to accompany the traditions of the Citralata and Pralata court servants as part of the ceremonial completeness, particularly during Garebek.